2021
DOI: 10.1111/jonm.13386
|View full text |Cite
|
Sign up to set email alerts
|

Work environment and person‐centred dementia care in nursing homes—A cross‐sectional study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…Addressing divergent care values, processes, priorities, staff turnover and low foundational knowledge has the potential to create and sustain functional teams and support teamwork critical to person-centred practices, (cf. Kong et al, 2022;Oppert et al, 2018;Rutten et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Addressing divergent care values, processes, priorities, staff turnover and low foundational knowledge has the potential to create and sustain functional teams and support teamwork critical to person-centred practices, (cf. Kong et al, 2022;Oppert et al, 2018;Rutten et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It was stressed that education and/or in‐house training possibilities are of great importance in addressing this gap. Previous research has shown that when staff share the same care philosophy, continuing education on dementia and regular supervision is associated with a higher degree of person‐centredness (Rutten et al., 2021; Sjögren et al., 2017). However, having low foundational knowledge may also imply that staff are set to provide care beyond their competence and expertise, hindering all efforts to promote PCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable is that several of the positive factors attributed to the influence of the expert coaches pertained to behavioural qualities, such as employees’ sense of urgency, commitment, and open communication. Although such behavioural factors are known to have a large impact on the effectiveness of QI [ 30 ], they are also elusive and notoriously difficult to change. According to interviewees, the frequent and long-term presence of the expert coaches, in combination with their independent position, helped to create a climate of openness and trust in which new routines could be shaped and practised [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…RCC facilitates a holistic view of the resident, recognising residents’ preferences and values, promotes autonomy, and right to self-determination. RCC emphasises partnerships between the health- carer and resident, in addition to care flexibility in attempt to contribute to meaningful lives and promote well-being for the residents [ 37 39 ].…”
Section: Introductionmentioning
confidence: 99%